1995
DOI: 10.1080/02772249509358131
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lactic acid content and activity of lactate dehydrogenase inclarias batrachus, exposed to carbaryl

Abstract: Ciarias batrachus, the fresh water teleost, were exposed to subacute concentrations (1,2 and 4 mg/L) of carbaryl (LC50; 15.08 mg/L) for 96 hr and 15 days. Its effect on lactic acid content and the activity of lactate dehydrogenase (LDH) in various tissues and blood of the fish was investigated. Carbaryl at all concentrations tested and both incubation periods caused accumulation of lactic acid in different fish tissues; the level being higher at 96 hr than that at 15 days. In blood, lactic acid concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Some components present in the fertilizer industrial effluent interact together and produce toxicity to aquatic organisms for example the interaction between dissolve oxygen and elevated ammonia has been shown to alter the respiratory physiology of fresh water fish (Pickering and Pottinger 1987). These findings indicated that the inhibitory effect of industrial effluent on the activity of LDH may be mediated via formation of enzyme-inhibitor complex leading to impairment of carbohydrate metabolism (Panepucci et al 1984(Panepucci et al , 1987Copper and Somero 1990;Sharma and Gopal 1995).…”
Section: Resultsmentioning
confidence: 96%
“…Some components present in the fertilizer industrial effluent interact together and produce toxicity to aquatic organisms for example the interaction between dissolve oxygen and elevated ammonia has been shown to alter the respiratory physiology of fresh water fish (Pickering and Pottinger 1987). These findings indicated that the inhibitory effect of industrial effluent on the activity of LDH may be mediated via formation of enzyme-inhibitor complex leading to impairment of carbohydrate metabolism (Panepucci et al 1984(Panepucci et al , 1987Copper and Somero 1990;Sharma and Gopal 1995).…”
Section: Resultsmentioning
confidence: 96%
“…This indicates that dietary high vitamin C can reduce LDH activity inhibition by deltamethrin. The inhibition in the LDH activity due to deltamethrin exposure could either be due to changes in the conformation of active site [42], formation of enzyme-inhibitor complex leading to impairment of carbohydrate metabolism [43,44] or reduction in de novo synthesis of proteins (enzymes).…”
Section: Discussionmentioning
confidence: 99%
“…The results are in agreement with the observations reported in freshwater crab exposed to methyl parathion,16 in rat treated with carbofuran14 and in C. batrachus exposed to sublethal concentrations of carbaryl. 15 The results of in-vitro studies conducted to determine the e †ect of carbofuran showed that the pesticide strongly inhibited the activity of LDH isolated from the tissues of C. batrachus (Singh, R. K. & Sharma, B. unpublished data). The Ðnding suggested that the inhibitory e †ect of organocarbamate pesticides on this terminal glycolytic enzyme may be due to the formation of enzymeinhibitor complex, thereby reducing the activity of LDH leading to impairment of carbohydrate metabolism in C. batrachus.…”
Section: Discussionmentioning
confidence: 99%